Remission of Ulcerated Necrobiosis Lipoidica Diabeticorum after Bariatric Surgery. (16th May 2013) - Bozkurt, Suleyman; Coskun, Halil; Kadioglu, Huseyin; Memmi, Naim; Cipe, Gokhan; Ersoy, Yeliz Emine; Lebe, Banu; Muslumanoglu, Mahmut
Abstract : A 32-year-old woman with type 2 diabetes mellitus suffering from morbid obesity with BMI 45, 14 kg/m 2 was operated on. Not only the type 2DM but also one of its complication known as necrobiosis lipoidica diabeticorum remitted postoperatively. Obesity should no longer be regarded simply as a cosmetic problem affecting certain individuals but an epidemic that threatens global well-being. It causes or exacerbates many health problems, and in particular, it is associated with the type 2 diabetes. Necrobiosis lipoidica is a granulomatous skin disease of unknown etiology, associated mainly with diabetes mellitus. We presented in this paper a morbid obese case of necrobiosis lipoidica diabeticorum with dramatic good response to bariatric surgery.